2008
DOI: 10.1038/sj.bjc.6604442
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed plus carboplatin in elderly patients with malignant pleural mesothelioma: combined analysis of two phase II trials

Abstract: The incidence of malignant pleural mesothelioma (MPM) in elderly patients is increasing. In this study, pooled data from two phase II trials of pemetrexed and carboplatin (PC) as first-line therapy were retrospectively analysed for comparisons between age groups. Patients received pemetrexed 500 mg m À2 and carboplatin AUC 5 mg ml À1 min À1 intravenously every 21 days with standard vitamin supplementation. Elderly patients were defined as those X70 years old. A total of 178 patients with an ECOG performance st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(44 citation statements)
references
References 37 publications
4
40
0
Order By: Relevance
“…7 m o n t h s , r e s p e c t i v e l y ( 2 4 ) . Furthermore, a secondary combined analysis of two of these trials found that this combination was well tolerated and had a similar level of activity in elderly patients (≥70 years), compared with younger ones (26). These results are similar to those with the cisplatin-based combination.…”
Section: First-line Combination Ctsupporting
confidence: 76%
“…7 m o n t h s , r e s p e c t i v e l y ( 2 4 ) . Furthermore, a secondary combined analysis of two of these trials found that this combination was well tolerated and had a similar level of activity in elderly patients (≥70 years), compared with younger ones (26). These results are similar to those with the cisplatin-based combination.…”
Section: First-line Combination Ctsupporting
confidence: 76%
“…In our study, we retrospectively evaluated whether the expression of ERCC1 or TS and their main functional polymorphisms could predict clinical outcome in a homogeneous population of 99 MPM patients treated with the carboplatin/pemetrexed regimen described in our previous studies (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with MPM are unfit to receive the cisplatin-based chemotherapy due to the increasing incidence of the disease in the elderly population and the poor performance status often observed at onset. Pemetrexed alone (6) or combined with carboplatin (7,8) has been proposed as alternative treatment choices for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the lack of randomized evidence, carboplatin is often substituted for cisplatin due to simpler administration and perceived lower toxicity. There have been no direct phase III comparisons between the two platinum agents, although phase I and II studies have shown similar activity and similar objective radiological response rates of either in combination with pemetrexed [Ceresoli et al 2006[Ceresoli et al , 2008. Patients are often offered carboplatin in the setting of medical contraindications to cisplatin.…”
Section: First-line Chemotherapymentioning
confidence: 99%